Implementation of Character Education for Elementary School Students Through the Learning of Civic Education - Putri Erica Valendria; Widia Nur Jannah; Dewi Yulianawati (JED (Jurnal Etika Demokrasi), 2023)
The objectives of this study were to: (1) collect and describe information on character education's application to fourth-graders at SDN 1 Palimanan Barat. (2) to gather and describe information regarding the character traits that SDN 1 Palimanan Barat fourth-graders exhibit. (3) to gather information about the school's efforts to implement character education at SDN 1 Palimanan Barat and to describe that information. This study employs a descriptive qualitative research design and uses methods like observation, interviews, recording, and questionnaires to gather data. 61 class IV students and class IV teachers served as the study's primary participants, although only 30 students from class IV B were selected for the questionnaire's sample size. Additionally, the principle of SDN 1 Palimanan Barat is the final topic. The findings of this study can be deduced from the planning of learning, the application of knowledge, and the facilitating and impeding elements of character education performance. Researchers claim that because many character education values, including religious, social, moral, responsible, environmental, creative, and social values like commitment and tolerance, are ingrained in students, the implementation of student character education in civics learning is quite good.